Mapping 21st Century Global Coastal Land Reclamation. Issue 2 (9th February 2023) - Sengupta, Dhritiraj; Choi, Young Rae; Tian, Bo; Brown, Sally; Meadows, Michael; Hackney, Christopher R.; Banerjee, Abhishek; Li, Yingjie; Chen, Ruishan; Zhou, Yunxuan
Abstract: Increasing population size and economic dependence on the coastal zone, coupled with the growing need for residential, agricultural, industrial, commercial and green space infrastructure, are key drivers of land reclamation. Until now, there has been no comprehensive assessment of the global distribution of land use on reclaimed space at the coast. Here, we analyze Landsat satellite imagery from 2000 to 2020 to quantify the spatial extent, scale, and land use of urban coastal reclamation for 135 cities with populations in excess of 1 million. Findings indicate that 78% (106/135) of these major coastal cities have resorted to reclamation as a source of new ground, contributing a total 253, 000 ha of additional land to the Earth's surface in the 21st century, equivalent to an area the size of Luxembourg. Reclamation is especially prominent in East Asia, the Middle East, and Southeast Asia, followed by Western Europe and West Africa. The most common land uses on reclaimed spaces are port extension (>70 cities), followed by residential/commercial (30 cities) and industrial (19 cities). While increased global trade and the rapid urbanization have driven these uses, we argue that a city's prestigious place‐making effort to gain global reputation is emerging as another major driver underlying recent reclamation projects to create tourist and green spaces Meanwhile, the study suggests that 70% of recent reclamation has occurred in areas identified as potentially exposed to extreme sea level rise (SLR) by 2100 and this presents a significant challenge to sustainable development at the coast. Plain Language Summary: Coastal regions face enormous pressure from growing human footprints, especially given the current rates of sea‐level rise. It is now recognized that seawards extension of the land through land reclamation and infrastructure development, at least partly in response to increased vulnerability induced by extreme storm surge events, is also a feature of recent coastal dynamics, especially in the world's coastal megacities Despite its growing global importance and reach worldwide, coastal reclamation is regarded as a local issue. Subsequently, the scale, intensity, and justification are not globally known, rather they are documented through localized case studies. By leveraging advanced satellite and cloud computing technology, this study aims to map the global state of 21st coastal land reclamation and to highlight the risk of such an anthropogenic footprint at the coast in the era of SLR. Key Points: 253, 000 ha of additional land to the Earth's coastal surface in the 21st century, equivalent to an area the size of Luxembourg Coastal Reclamation is especially prominent in East Asia, the Middle East, and Southeast Asia, followed by Western Europe and West Africa We suggest that 70% of recent reclamation has occurred in areas identified as high risk to extreme SLR by 2100